Constructing a conceptual framework on integrating the Asma Ul Husna values into the conventional design process - Norzaman, Nor Ziratul Aqma; Abd Rahman, Khairul Aidil Azlin (Malaysia Technical Scientist Association, 2018)
Nowadays, most industrial designers utilise secular design approach in designing products by implementing user-centred approach, which focuses on profit maximisation and human satisfaction. This practice is found not to be assimilated and contradicting with religion-oriented approach. It can also be considered incomplete because it only concentrates on duniawi. Unconsiously, the idea of fulfilling human wants and needs leave no option but to prioritise consumer over Allah. At the same time, they unintentionally encourage consumers to keep on seeking worldly paradise. This is contradicting with Islamic thoughts and practices. Therefore, there is a need to provide a guideline for designers by constructing a conceptual framework on integrating the Asma ul Husna values into the conventional desin process for the benefit of ummah. As an overview, this paper provides arguments about the significance to reorientate the conventional design process based on Islamic perspective of view. Infusion of Islamic knowledge by integrating the Asma ul Husna values believed to be the best solution, as gudeline in nurturing holistic and excellent designers who not only excel in duniawi but ukhrawi as well.